Polydiacetylene Micelles in Nanomedicine and Beyond - Gravel, Edmond; Demeese, Céline; Doris, Eric (Synlett, 2024)
In this account article, we give an overview of our contribution to the development of stable micellar carriers obtained by self-assembly and photo-polymerization of diacetylenic amphiphiles. The stabilized micelles can be loaded with active substances and used for diagnostic and therapeutic applications, or loaded with a metal catalyst to promote some synthetic transformations in fully aqueous medium.Table of content1 Introduction2 Polydiacetylene Micelles Applied to Nanomedicine2.1 From Amphiphilic Units to Micelles2.2 In vivo Behavior of Micelles2.3 Passive Targeting of Tumors with Micelles2.4 Drug Delivery with Micelles2.5 Towards Improved Delivery of Micelles to Tumors Using Sonoporation2.6 Active Targeting with Micelles2.7 Behavior of Micelles at the Cellular Level and Potential Cytotoxicity2.8 Micelles for siRNA Transfection3 Polydiacetylene Micelles Applied to Catalysis3.1 Copper Nanoparticles in Micelles3.2 Copper Salts in Micelles4 Conclusion
Keywords: micelle; nanomedicine; polydiacetylene; catalysis; self-assembly